Practical considerations in choosing a factor VIII prophylaxis regimen: Role of clinical phenotype and trough levels - Ljung, Rolf; Fischer, Kathelijn; Carcao, Manuel; Santagostino, Elena; Manco-Johnson, Marilyn J.; Mathew, Prasad (Thrombosis and Haemostasis, 2016)
Current therapy for haemophilia A is guided by severity of the disease, which in turn is best reflected in patients' endogenous factor VIII activity levels. For patients with severe haemophilia (particularly children), prophylaxis with continuous routine factor replacement has become standard of care in developed countries and is gradually becoming the standard of care in developing countries. The question arises then: what is an appropriate prophylaxis regimen to prevent bleeding events and arthropathy, while also maximizing patient quality of life and taking into consideration the costs of prophylaxis? Should all patients be treated with one standard, fixed prophylaxis regimen, or should prophylaxis be individualised for each patient? If so, what factors need to be considered in choosing the appropriate dose and frequency of factor administration? If prophylaxis is tailored to the individual patient, then patient-related factors (bleeding phenotype, activity profiles, age, joint status) and product-specific factors (half-life of the replacement factor in the individual patient) will determine the choice of regimen, whether it be a fixed-regimen prophylaxis or prophylaxis that is tailored to patient activity and bleeding risk. Regardless of the choice of prophylaxis regimen, for any regimen to be effective, adherence to therapy is key to optimising outcomes.
Keywords: FVIII; prophylaxis; phenotype; dose; frequency